مساهمة براءة الاختراع في تطوير المؤسسات الناشئة - مخناش ر وميساء قلاتي فاطمة أمينة (ب ا خءة الاخت ا خ ، السؤسدات الشاشئة، الابتكار، الابجا ., 2024)
Emerging enterprises participate significantly to achieve local development، increasing local production، and in the integration with large enterprises. In order for them to be able to enhance their competitiveness and ensure their survival and continuity in performing their activities، they must benefit from the characteristics and privileges that patent rights add to them as an element of industrial property، and then by emerging The extent to which emerging enterprises need a patent so that they can reap the benefits of these rights and develop their activity.
Keywords: patent، emerging institutions، innovation، creativity